The Bibliometric and Visualized Analysis of Research for Hospital Medication Management Based on the Web of Science Database - Hu C; Sheng M; Wang K; Yang Z; Che S (Dove Medical Press, 2024)
Chenxiao Hu,* Mingwei Sheng,* Ke Wang,* Zi Yang, Shiping Che Solicitation Office, The First Hospital of Lanzhou University, Lanzhou, Gansu, People's Republic of China*These authors contributed equally to this workCorrespondence: Shiping Che, The First Hospital of Lanzhou University, No. 1 Donggang West Road, Lanzhou, Gansu, 730000, People's Republic of China, Email ldyycheshiping@163.comObjective: Identify the collaborations between authors, countries, and institutions, respectively, and explore the hot issues and prospects for research on hospital medication management.Materials and Methods: Publications on hospital medication management were retrieved from the Web of Science Core Collection. Bibliometric analyses were performed using CiteSpace 6.1.R3, HistCite 2.1, and VOSviewer 1.6.16. The network maps were created between authors, countries institutions, and keywords.Results: A total of 18,723 articles related to hospital medication management studies were identified. Rapid growth in the number of publications since 2017. The high papers were published in AM J HEALTH-SYST PH, while JAMA-J AM MED ASSOC was the most co-cited journal. Manias E and WHO ranked first in the author and cited author. There were active collaborations among the top authors. Bates DW was the key author in this field. The authors have active collaborations in adverse drug events, acute coronary syndrome, in-hospital major bleeding, and so on. The US was the leading contributor in this field. The UK, Australia, and China are also very active. Active cooperation between countries and between institutions was observed. The main hot topics included matters related to outcome indicators, hospital pharmacy service behaviors, and medication use in pain management. More recent keywords focus on chronic disease medication management and clinical medication management.Conclusion: Hospital medication management studies have significantly increased after 2017. There was active cooperation between authors, countries, and institutions. The application of hospital medication management in the emergency department and the relationship between medication management and medication adherence are current research hotspots. In addition, with the continuous progress of society, chronic diseases have become an important factor affecting people's health, and medication management is becoming more and more subdivided, so the direction of chronic disease medication management as well as precise medication may become the development direction of future research.Keywords: bibliometric analysis, medication management, hospital, development trends, hot topics